Proinflammatory (CD14+CD16++) monocytes in type 2 diabetes mellitus patients with/without chronic periodontitis - Raghunathan Jagannathan; Malini Thayman; Suresh Ranga Rao (Wolters Kluwer Medknow Publications, 2019)
Background: Until date, the proportion of nonclassic monocytes in type 2 diabetic mellitus patients with and without chronic periodontitis has not been evaluated based on glycemic control. The objective of this study was to compare the proportion of CD14+CD16++ monocytes in type 2 diabetic patients with and without chronic periodontitis. Materials and Methods: In this cross sectional study A total of sixty individuals with type 2 diabetes mellitus (n = 15/group) were recruited. Individuals were grouped based on glycosylated hemoglobin A (HbA 1c) values and the presence of chronic periodontitis; Group 1 (diabetes mellitus with good glycemic control), Group 2 (diabetes mellitus with poor glycemic control), Group 3 (diabetic mellitus with chronic periodontitis and good glycemic control), Group 4 (diabetic mellitus with chronic periodontitis and poor glycemic control). Fluorochrome-conjugated monoclonal antibodies against CD14, CD16, and human leukocyte antigen-antigen D related was used to analyze the proportion of nonclassic monocytes by flow cytometry. One-way ANOVA with Tukey's post-hoc test was used to assess the significant differences in monocyte subpopulations. The Pearson's correlation test was used to assess the relationship between hemoglobin A1c values and percentage of nonclassical monocytes. In both the above statistical tools, the value of P < 0.05 is considered as significant level. Results: Group 4 had the highest percentage of CD14+CD16++ monocytes 14.67% + 4.70%, followed by Group 3-9.73% + 0.60%, Group 2-9.32% + 2.03% and Group 1-5.92% + 0.63% (P < 0.001). Further, a statistically significant positive correlation between HbA (1c) levels and the proportion of CD14+CD16++ monocytes was observed. Conclusion: In the present study, we observed type 2 diabetes mellitus patients with poor glycemic control and chronic periodontitis showed more than two-fold increase in the proportion of nonclassic monocytes compared to type 2 diabetes mellitus patients with good glycemic control.